Dendritic spines in the hippocampus of Genetic Absence Epilepsy Rats (GAERS): An ultrastructural quantitative analysis - (:unkn) unknown (My University, 2003)
Objective: The aim of the present study was to analyze the area of glutamate immunoreactive (-ir) dendritic spines in CA3 and dentate gyrus hilar regions in Genetic Absence Epilepsy Rats from Strasbourg (GAERS) hippocampus by electron microscopy in order to investigate possible glutamate-induced morphological changes in dendritic spines. Methods: GAERS and non-epileptic control (NEC) rats were used. The brains were removed after perfusion fixation and CA3 and dentate hilar regions of the hippocampus were studied using immunogold electron microscopical methods. The area of dendritic spines was measured with the program NIH Image Analysis. Results: There was no significant difference in the mean number of glutamate-ir spines making asymmetric synapses per mossy terminal in CA3 and dentate hilar regions compared to the control group. No significant difference in the area of glutamate-ir dendritic spines making asymmetric synapses with mossy fiber terminals between NEC and GAERS groups was found. Conclusion: Dendritic spines in the hippocampus seem not to be affected in absence epilepsy, as opposed to those in temporal lobe epilepsy (TLE). This may be due to differences in pathogenetic mechanisms between TLE and absence epilepsy.
Keywords: Dendritic spine; GAERS; Hippocampus; Ultrastructure